Sex and Drugs before Rock 'n' Roll : Youth Culture and Masculinity during Holland's Golden Age - Roberts, Benjamin, 1965- (Book collections on Project MUSE., 2012)
Sex and Drugs Before the Rock 'n' Roll is a fascinating volume that presents an engaging overview of what it was like to be young and male in the Dutch Golden Age. Here, well-known cohorts of Rembrandt are examined for the ways in which they expressed themselves by defying conservative values and norms. This study reveals how these young men rebelled, breaking from previous generations: letting their hair grow long, wearing colorful clothing, drinking excessively, challenging city guards, being promiscuous, smoking, and singing lewd songs. Cogently argued, this study paints a compel.